1991
DOI: 10.1002/ejsp.2420210302
|View full text |Cite
|
Sign up to set email alerts
|

Social influence: The role of originality

Abstract: Two experiments used 150 undergraduates to investigate the role of message originality vs conventionality in social influence. It was hypothesized that Ss would generate more original proposals when confronted with a minority advocating an original viewpoint than when confronted with a conventional minority proposal or with an original majority proposal. Results of Exp 1 support the hypothesis. Exp 2 further demonstrated that the original message induced creative processing only when attributed to a minority s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 17 publications
2
25
1
Order By: Relevance
“…The process of majority influence is classically regarded as the conversion or conformity of one person in accordance with the position or wishes expressed by others belonging to others comprising a majority (Meyers & Brashers, 1999;Meyers, Brashers & Hanner, 2000;Mucchi-Faina, Maass & Volpato, 1991). For example, Asch's (1951) popularly cited works indicated that people can be pressured into reporting an obviously incorrect answer regarding a physical stimulus based solely on the majority's expression of a divergent viewpoint.…”
Section: Majority and Minority Influencementioning
confidence: 99%
See 4 more Smart Citations
“…The process of majority influence is classically regarded as the conversion or conformity of one person in accordance with the position or wishes expressed by others belonging to others comprising a majority (Meyers & Brashers, 1999;Meyers, Brashers & Hanner, 2000;Mucchi-Faina, Maass & Volpato, 1991). For example, Asch's (1951) popularly cited works indicated that people can be pressured into reporting an obviously incorrect answer regarding a physical stimulus based solely on the majority's expression of a divergent viewpoint.…”
Section: Majority and Minority Influencementioning
confidence: 99%
“…Others have observed that minority members expressing opinions or viewpoints divergent from the majority are often met with hard or aggressive influence tactics from the majority members including pressure, derision, or ridicule, especially during the early stages of the interaction (Nemeth & Wachtler, 1983). However, minority influence has proven successful for the internalization of divergent viewpoints or opinions, but only when the arguments and persuasive appeals communicated to others are of high quality or originality as compared to those rendered from the majority position (Meyers & Brashers, 1999;Mucchi-Faina et al, 1991). Finally, Meyers et al (2000) found that successful minority subgroups were more likely than majority subgroups to express agreement or acknowledgement of others during their influence attempts, were more likely to object or challenge assertions and propositions, and make greater use of contextual or framing statements to qualify a point of contention, or forestall the possibility of potential refutation by securing additional a priori agreement or removing possible objections before they could be aired.…”
Section: Majority and Minority Influencementioning
confidence: 99%
See 3 more Smart Citations